Presentation and use of a new diagram to determine the facies and the origins of water: The 3rd Parfait-Hounsinou diagram - Sagnon Parfait Hounsinou (Heliyon, 2023)
To determine the origin of groundwater mineralization, it is often necessary to produce Piper or Schoeller-Berkaloff or Stiff or Durov diagrams, to calculate the Revelle index or the basic exchange index.In this new method, the Reports rCl−rHCO3−+rCO32−, rSO42−+rNO3−rHCO3−+rCO32−, rNa++rK+rCa2+ , rMg2+rCa2+ and rNa++rK+rCl− are represented by 5 points on the 3rd Parfait-Hounsinou diagram which makes its interpretation faster than the interpretation of the Scholler-Berkaloff and Stiff diagrams which have 7 and 6 representative points respectively. The 3rd Parfait-Hounsinou diagram is more precise and gives more information than the diagrams of Piper, Scholler-Berkaloff and Stiff on the origin of the mineralization of water. The Parfait-Hounsinou table makes it possible to identify the facies and the origin of the mineralization of an infinity of water samples. The 3rd Parfait-Hounsinou diagram and the table of Parfait-Hounsinou were used to study the waters of 44 wells in the town of Abomey-Calavi in Benin and the results obtained were compared to those results obtained using the Scholler-Berkaloff and Stiff diagrams. The Parfait-Hounsinou table and the 3rd Parfait-Hounsinou diagram showed that 79.22% of the waters studied have a sodium potassium chloride facies, 13.63% of these waters have a sodium potassium bicarbonate facies, 2.27% of these waters have a sodium potassium sulfate facies and 2.27% of these waters have a calcium sulfate facies. They revealed that for 86.63% of the well water studied, clay minerals capture the Ca2+ and Mg2+ ions present in groundwater and release Na+ and K+ ions into the water in exchange. They also revealed that there is seawater intrusion in 4.54% of the waters studied, all located in the coastal village of Togbin. The results obtained during this study confirm those obtained previously in the study area using multiple methods. The novelty brought by the 3rd Parfait-Hounsinou diagram and the table of Parfait-Hounsinou is that they are more precise and make it possible to obtain more information on the facies and the origin of the mineralization of the water samples than the diagrams of Piper, Schoeller-Berkaloff, Stiff and Durov.